Development of library branch in the Republic of Kazakhstan - Онгарова, Л. Н. (Journal of Economic Research & Business Administration, 2015)
The relation to libraries sharply changed around the world. Modern Kazakhstan society starts to understand that libraries are important for informing of citizens, transparency of management, and also for creation of «the electronic government».